Multi-Robot Cooperation using Immune Network with Memory - Razali, Sazalinsyah; Meng, Qinggang; Yang, Shuang-Hua (2009)
In this paper, basic biological immune systems and their responses to external elements to maintain an organism's health state are described. The relationship between immune systems and multi-robot systems are also discussed. Our proposed algorithm is based on immune network theories that have many similarities with the multi-robot systems domain. The paper describes a memory-based immune network that enhance a robot's action-selection process and can obtain an overall a quick group response. The algorithm which is named as Immune Network T-cell-regulated-with Memory (INT-M) is applied to the dog and sheep scenario. Simulation experiments were conducted on the Player/Stage platform and experimental results are presented.